Pathogen infection induces specific transgenerational modifications to gene expression and fitness in Caenorhabditis elegans - Wibisono, Phillip; Sun, Jingru (Frontiers in Physiology, 2023)
How pathogen infection in a parental generation affects response in future generations to the same pathogen via epigenetic modifications has been the topic of recent studies. These studies focused on changes attributed to transgenerational epigenetic inheritance and how these changes cause an observable difference in behavior or immune response in a population. However, we questioned if pathogen infection causes hidden epigenetic changes to fitness that are not observable at the population level. Using the nematode Caenorhabditis elegans as a model organism, we examined the generation-to-generation differences in survival of both an unexposed and primed lineage of animals against a human opportunistic pathogen Salmonella enterica. We discovered that training a lineage of C. elegans against a specific pathogen does not cause a significant change to overall survival, but rather narrows survival variability between generations. Quantification of gene expression revealed reduced variation of a specific member of the TFEB lipophagic pathway. We also provided the first report of a repeating pattern of survival times over the course of 12 generations in the control lineage of C. elegans. This repeating pattern indicates that the variability in survival between generations of the control lineage is not random but may be regulated by unknown mechanisms. Overall, our study indicates that pathogen infection can cause specific phenotypic changes due to epigenetic modifications, and a possible system of epigenetic regulation between generations.